Pengaruh Kualitas Sistem Informasi Akademik terhadap Kepuasan dan Loyalitas Mahasiswa Perguruan Tinggi - Astri Ayu Purwati; Muhammad Luthfi Hamzah; Hamzah Hamzah; Sarli Rahman (COSTING : Journal of Economic, Business and Accounting, 2018)
With the increasing speed of information flow due to globalization, the role of information technology is vital and very decisive for an educational institution in increasing its ability to face competition and be able to provide satisfactory services for students. The object of this research is the users of the university's academic information system, namely all active students of TA Geap 2017-2018 with a sample of 450 people. The data analysis technique used in this study is using Structural Equation Modeling (SEM) Amos. The results of the study show that improving the quality of academic information systems will be able to increase student satisfaction but not necessarily be able to increase student loyalty directly. However, indirectly through satisfaction, the quality of the system can increase user / student loyalty. Improvement and improvement of academic information also through this research directly and indirectly can have an impact on increasing student satisfaction and loyalty. Good service quality in a college is a very important assessment in increasing student satisfaction and loyalty. Keywords: Information Technology, Satisfaction, Loyalty